Hak Keperdataan Anak Warga Negara Indonesia Yang Tergabung Dengan Organisasi Teroris Internasional - Muhammad Syam Riva'i; Davilla Prawidya Azaria (Veteran Law Review, 2024)
As the defeated Islamic State of Iraq and Syria (ISIS) raises neglected misfortune for Indonesian children whose parents once participated in the organization. Indonesia's Government's decision to repatriate has not yet been fully executed while circulating threatened punishment by the Government to withdraw the nationality of a person involved in ISIS to make it worse. In contrast, international law safeguards civil rights for children despite their status of unwillingly participating in terrorist organizations. Normative juridical research was conducted by taking statutory and conceptual approaches to examine national regulation of children's civil rights legal protection. The result shows that children's civil rights ex-ISIS remain valid as their indivisible fundamental rights while state compliance is necessary. Redefining children's status as children of terrorist network victims is mentioned in Article 59 (2) (k) of Law No. 35/2014 concerning Children's Protection. With a status as a victim, a particular procedure can be executed to restore and safeguard child civil rights. Ministry of Women Empowerment and Child Protection (Kemen PPPA) coordinates with National Counter Terrorism Agency (BNPT) mandates to exercise legal aid to provide education, counselling, rehabilitation, and social assistance.